Danger signals in oral cavity‐related diseases. Issue 1 (18th February 2019) - Kay, Jason G.; Kramer, Jill M.; Visser, Michelle B.
Abstract: The oral cavity is a unique environment containing teeth juxtaposed with soft tissues, all of which are constantly bathed in microbial products and host‐derived factors. While microbial dysbiosis in the oral cavity clearly leads to oral inflammatory disease, recent advances find that endogenous danger‐associated molecular patterns (DAMPs) released from oral and salivary tissue also contribute to the progression of inflammatory and autoimmune disease, respectively. In contrast, DAMPs produced during oral fungal infection actually promote the resolution of infection. Here, we present a review of the literature suggesting a role for signaling by DAMPs, which may intersect with pathogen‐associated molecular pattern (PAMP) signaling, in diseases that manifest in the oral cavity, specifically periodontal disease, oropharyngeal candidiasis, and Sjögren's syndrome. Abstract : Review of how immune activation leading to signaling of danger signals contributes to the progression or resolution of oral diseases.